Annals of Clinical Psychiatry 2021
DOI: 10.12788/acp.0018
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality in patients with standard EEG findings of ‘diffuse slowing’

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
2
0
0
1
Order By: Relevance
“… 32 , 33 The present finding suggests that BSEEG may be useful for predicting both a short-term and a long-term mortality in elderly inpatients. This result is consistent with the recent prospective cohort study 10 and retrospective cohort study 11 showing that clinical electroencephalography slowing is associated with an increased mortality. Furthermore, short-term mortalities and relative risks in BSEEG-positive patients were higher in patients with dementia compared to those without dementia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 32 , 33 The present finding suggests that BSEEG may be useful for predicting both a short-term and a long-term mortality in elderly inpatients. This result is consistent with the recent prospective cohort study 10 and retrospective cohort study 11 showing that clinical electroencephalography slowing is associated with an increased mortality. Furthermore, short-term mortalities and relative risks in BSEEG-positive patients were higher in patients with dementia compared to those without dementia.…”
Section: Discussionsupporting
confidence: 93%
“… 9 In fact, we showed that BSEEG score can predict mortality of elderly inpatients better than clinical categorization of delirium. 9 Consistent with our previous findings of higher BSEEG score indicative of slow brain wave and its association with increased mortality, a recent prospective cohort study 10 and a retrospective cohort study 11 showed that clinical electroencephalography slowing is associated with higher mortality. However, there is neither a replication study for the utility of BSEEG nor an investigation of the utility of BSEEG for subjects with dementia.…”
Section: Introductionsupporting
confidence: 84%
“…Тип V означает, что у пациентов на первый план выступают уже не регуляторные, а структурные поражения в коре головного мозга. При наличии ЭЭГ данного типа есть все основания говорить о грубых (тяжелых) органических поражениях мозга [12,18]. В группе пациентов без ЭОПГМ такие изменения на ЭЭГ отсутствовали.…”
Section: таблица 2 частотный анализ встречаемости типов ээг (по еа жи...unclassified